Effect of repeat purchase and dynamic market size on diffusion of an innovative technological consumer product in a segmented market - Aggarwal, Sugandha; Gupta, Anshu; Govindan, Kannan; Jha, P. C.; Meidutė, Ieva (Technological and Economic Development of Economy, 2014)
This study develops diffusion models for technological consumer products under the marketing environment when a product is marketed in a segmented market and observes two distinctive promotional strategies of mass and differentiated promotion; an under explored study area. Mass promotion strategy creates a spectrum effect in market with an aim to create wider product awareness and influence the market size. Whereas the differentiated promotion strategy plays major role in external influence component in the respective segment and target for adoption by the current potential segment. Previous studies on segmented diffusion models assumed only first time purchase and constant market size which may yield underestimated results and fail to give appropriate insight of the diffusion process. The study develops and validates generalized diffusion models for segmented market incorporating the repurchase behaviour of the adopter population and dynamic potential market size considerations. Performance of the proposed models is analysed on real life data for a new product marketed in four segments and compared with the previous study.